A CRITICAL STUDY ON THE COALITION GOVERNMENT AND UNI-FEDERAL NATURE OF THE POWER SHARING IN INDIA (International Journal of Food and Nutritional Sciences, 2023)
The researcher has analysed both the legal and political aspects of the power-sharing agreement between the Union and the State Governments. The researcher is of the view that the provisions of the said agreement are constitutionally valid, but also finds that certain issues have been ignored by the government. In this regard, it is necessary to emphasize the fact that in the present agreement between the Union and the State Governments, it is recognized that there are powers with which the Union can influence the States indirectly. Therefore, in any arrangement made between the Union and the States, it is essential to have these powers for effective implementation of the policies of the Union. This may be a major reason for the present arrangement to exist. Another consideration is the position of the States in national affairs. Though the Constitution of India speaks of India as a nation, nevertheless, the States have to face various problems such as the ones referred to in the text. Therefore, in order to provide solutions to these problems, a certain amount of power sharing arrangement is needed between the States and the Union. This paper examines the nature of power sharing agreement in India.